2019
DOI: 10.1002/lipd.12139
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adipokine VASPIN Is Associated with Serum Lipid Profiles in Humans

Abstract: VASPIN, visceral adipose tissue‐derived serpin, is an adipokine ameliorating insulin resistance in obesity. Here, we investigated the role of VASPIN and its genetic variants in lipid metabolism. We measured serum VASPIN concentrations by ELISA in 823 metabolically well‐characterized Caucasian subjects (Sorbs from Germany). Furthermore, we genotyped 30 representative single nucleotide polymorphisms (SNP) in two independent cohorts with metabolic phenotyping, the Sorbs (N = 823) and Leipzig (N = 919), and conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(50 reference statements)
4
7
0
Order By: Relevance
“…In a previous study, we observed positive correlation between serum vaspin and TGs, which was further supported by MR analyses suggesting a causal impact on LDL‐chol [28]. In support of the metabolically beneficial action of vaspin in obesity [1, 2, 10, 28], the GECA and gene ontology enrichment analyses point out genes involved in lipid metabolic processes (e.g., low‐density lipoprotein receptor). Ultimately, our in vivo studies validated the involvement of vaspin in lipid metabolism by presenting reduced TG and lower FFA levels in vaspin‐treated mice.…”
Section: Discussionsupporting
confidence: 70%
“…In a previous study, we observed positive correlation between serum vaspin and TGs, which was further supported by MR analyses suggesting a causal impact on LDL‐chol [28]. In support of the metabolically beneficial action of vaspin in obesity [1, 2, 10, 28], the GECA and gene ontology enrichment analyses point out genes involved in lipid metabolic processes (e.g., low‐density lipoprotein receptor). Ultimately, our in vivo studies validated the involvement of vaspin in lipid metabolism by presenting reduced TG and lower FFA levels in vaspin‐treated mice.…”
Section: Discussionsupporting
confidence: 70%
“…The NPC1 (niemann-Pick Type C) gene on chromosome 23 that correlated with yearling weight participates in controlling the steady state of animal energy metabolism and plays an important regulatory role in body weight and fat metabolism [40][41][42]. The SERPINA12 (serpin family A member 12) gene on chromosome 18 that correlated with adult weight is closely associated with animal body composition and lipid distribution, and could serve as a marker for lipid metabolism [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Vaspin was originally isolated from the visceral adipose tissue of the Otsuka Long-Evans Tokushima fatty rat, an experimental model for type 2 diabetes mellitus (Hida et al, 2005). Consequently, its function has mostly been studied in the context of obesity and insulin resistance (Breitfeld et al, 2019;Youn et al, 2008). Inhibition thickness was defined as the distance between the granular layer and the basement membrane (dotted line) and was measured at 20 randomly selected locations for each biopsy using NIS-Elements BR 3.2 software (Nikon).…”
Section: Discussionmentioning
confidence: 99%